(untitled) (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2025)
Trademark disputes imply a linguistic battle over a term or a sequence of terms. Linguistic methods focusing on lexical, semantic and syntactic analysis can play an important role in assessing similarities, differences or the possibility of consumer confusion. The paper presents three real trademark cases from two distinguished linguists, who were called upon as expert witnesses to identify how lexical choices, semantic content and syntactic patterns can affect legal interpretation. Linguistic evidence withdrawn from corpus analysis can be very valuable in a trademark case. The work of the linguist consists in investigating how often the contested term appears in large corpora and in determining whether only the plaintiff has the right to use that certain word or not.